Hard X-ray selected giant radio galaxies – II. Morphological evidence of restarted radio activity. Issue 1 (19th March 2020) - Bruni, G; Panessa, F; Bassani, L; Dallacasa, D; Venturi, T; Saripalli, L; Brienza, M; Hernández-García, L; Chiaraluce, E; Ursini, F; Bazzano, A; Malizia, A; et al.
ABSTRACT: About 6 per cent of radio galaxies (RGs) can reach linear sizes larger than 0.7 Mpc, and are then classified as giant radio galaxies (GRGs). The conditions that make possible the formation of such big structures are still not clear – either core accretion properties or environmental factors. Recent studies have shown that GRGs can be up to four times more abundant in hard X-ray selected (i.e. from INTEGRAL /IBIS and Swift /BAT at >20 keV) RG samples. Moreover, a high fraction of young radio sources found in their cores suggest a recently restarted activity, as suggested from the discrepancy between the measured jet and lobes power, with respect to the one expected from core X-ray luminosity. Here, we present a radio morphological study of a sample of 15 hard X-ray selected GRGs, discussing low-frequency images from our GMRT campaign complemented with others from the literature: among them, 7/15 show evidence of restarted radio activity either in the form of double–double/X-shaped morphology, or as a cocoon emission embedding more recent jets. This, together with the objects from this sample already found hosting a young radio source in their core, suggests that at least 13 over 15 of these hard X-ray selected GRGs show features that are consistent with the possibility of restarted radio activity.